HLA-B*27 Heavy Chain Homo-Oligomers Promote the Cytotoxicity of NK Cells via Activation of PI3K/AKT Signaling - Hui-Chun Yu; Kuang-Yung Huang; Ming-Chi Lu; Hsien-Yu Huang Tseng; Su-Qin Liu; Ning-Sheng Lai; Hsien-Bin Huang (Medicina, 2022)
Background and Objectives: Ankylosing spondylitis (AS) is a chronic inflammatory disease and is highly linked with the expression of the human leukocytic antigen-B*27 (HLA-B*27) genotype. HLA-B*27 heavy chain (B*27-HC) has an innate characteristic to slowly fold, resulting in the accumulation of the misfolded B*27-HC and the formation of homo-oligomeric B*27-HC molecules. The homo-oligomeric B*27-HC can act as a ligand of KIR3DL2. Interaction of the homo-oligomeric B*27-HC molecules with KIR3DL2 will trigger the survival and activation of KIR3DL2-positive NK cells. However, the effects of homo-oligomeric B*27-HC molecules associated with KIR3DL2 on the cytotoxic activity of NK cells and their cytokine expressions remain unknown. Materials and Methods: HLA-B*-2704-HC was overexpressed in the HMy2.C1R (C1R) cell line. Western blotting and quantitative RT-PCR were used to analyze the protein expression and cytokine expression, respectively, when C1R-B*-2704 cells that overexpress B*2704-HC were co-cultured with NK-92MI cells. Flow cytometry was used to analyze the cytotoxicity mediated by NK-92MI cells. Results: Our results revealed that NK-92MI cells up-regulated the expression of perforin and enhanced the cytotoxic activity via augmentation of PI3K/AKT signaling after co-culturing with C1R-B*2704 cells. Suppression of the dimerized B*27-HC formation or treatment with an inhibitor of PI3K, LY294002, or with an anti-B*27-HC monoclonal antibody can reduce the perforin expression of NK-92MI after co-culturing with C1R-B*-2704. Co-culturing with C1R-B*-2704 cells suppressed the TNF-α and IL6 expressions of NK-92MI cells. Conclusion: Stimulation of NK cell-mediated cytotoxicity by homo-oligomeric B*27-HC molecules may contribute to the pathogenesis of AS.